Phthalate Exposures, DNA Methylation and Adiposity in Mexican Children Through Adolescence - Bowman, Alison; Peterson, Karen E.; Dolinoy, Dana C.; Meeker, John D.; Sánchez, Brisa N.; Mercado-Garcia, Adriana; Téllez-Rojo, Martha M.; Goodrich, Jaclyn M. (Frontiers in Public Health, 2019)
Phthalates are a class of endocrine disrupting chemicals with near ubiquitous exposure to populations around the world. Phthalates have been associated with children's adiposity in previous studies, though discrepancies exist across studies that may be due to timing of exposure or outcome assessment and population differences (i.e., genetics, other confounders). DNA methylation, an epigenetic modification involved in gene regulation, may mediate the effects of early life phthalate exposures on health outcomes. This study aims to evaluate the mediating effect of DNA methylation at growth-related genes on the association between phthalate exposure and repeat measures of adiposity (BMI-for-age z-score, waist circumference, and skinfolds thickness) in Mexican children. Urinary phthalate metabolite concentrations were quantified in mothers at each of the three trimesters of pregnancy and in children at the first peri-adolescent study visit. Blood leukocyte DNA methylation at H19 and HSD11B2 was quantified during the first peri-adolescent visit, and adiposity was measured at the first visit and again ~3 years later among participants (n = 109 boys, 114 girls) from the Early Life Exposure in Mexico to Environmental Toxicants (ELEMENT) project. Associations between phthalates or DNA methylation and repeat outcome measures were assessed separately in boys and girls using generalized estimating equation models including covariates (urinary specific gravity, maternal education, and child's age). Sobel tests were used to assess DNA methylation as a mediator in models adjusting for the same covariates. Associations between phthalates and adiposity varied by phthalate and timing of exposure. Early gestation MBP, MIBP, and MBzP were associated with adiposity among girls. For example, among girls first trimester maternal urine concentrations of MIBP were associated with increases in skinfold thickness, BMI-for-age, and waist circumference (p < 0.01). Second trimester and adolescent MBzP were associated with adiposity among boys in opposite directions. In girls, H19 methylation was positively associated with skinfold thickness. No significant mediation of phthalate exposure on adiposity by DNA methylation of H19 or HSD11B2 was observed (Sobel p > 0.05). However, the mediation analysis was underpowered to detect small to medium effect sizes, and the role of DNA methylation as a mediator between phthalates and outcomes merits further study.